2019
DOI: 10.1177/0193945919894709
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Body Image Perception among African American Women

Abstract: Obesity is a significant health problem in the US with African American (AA) women having one of the highest prevalence of obesity. Some AA women may equate a larger BMI with a positive body image. The purpose of this cross-sectional descriptive study was to examine the relationship between demographic variables, body image perception, coping behaviors and BMI with a non-probability sample of 191 AA women, 18–40 years old. Participants completed a demographic form and Pulver’s Figure Rating Scale (PFRS). Weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In the logistic regression model, body image perception and perception regarding activities were positively related to hypertension and high blood pressure among the studied group where activity perception was detected as one of the best predictors of hypertension. Ford and Pickett also supported the present findings, and they have shown that hypertension and BMI were predictors of body image perception [9]. There are limitations in this study, as the study design itself is cross-sectional.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the logistic regression model, body image perception and perception regarding activities were positively related to hypertension and high blood pressure among the studied group where activity perception was detected as one of the best predictors of hypertension. Ford and Pickett also supported the present findings, and they have shown that hypertension and BMI were predictors of body image perception [9]. There are limitations in this study, as the study design itself is cross-sectional.…”
Section: Discussionsupporting
confidence: 85%
“…are associated with the high prevalence of hypertension across different populations [2,3,[6][7][8]. A recent study also showed that people's body image might be a good predictor of hypertension [9].…”
Section: Introductionmentioning
confidence: 99%
“…BMI and %BF were positively correlated with BI concern in the ballet dancers and sedentary women. Some studies suggest that the higher the BMI and %BF, the greater BI dissatisfaction, confirming that women aim for a slim body [ 62 , 63 ]. %BF was negatively correlated with behaviors for anorexia in gym users.…”
Section: Discussionmentioning
confidence: 99%